EDGE-M3: A dynamic general equilibrium micro-macro model for the EU member states - Diego D'Andria; Jason DeBacker; Richard W. Evans; Jonathan Pycroft; Wouter Van Der Wielen; Magdalena Zachlod-Jelec (European Commission, Joint Research Centre (JRC), 2020)
This paper provides a technical description of the overlapping generations model used by the Joint Research Centre to analyse tax policy reforms, including in particular pension and demographic issues. The main feature of the EDGE-M3 model lies in its high level of disaggregation and the close connection between microeconomic and macroeconomic mechanisms which makes it a very suitable model to analyse the redistributive impact of policies. EDGE-M3 features eighty generations and seven earnings-ability types of individuals. To facilitate a realistic dynamic population structure EDGE-M3 includes Eurostat's demographic projections. In terms of calibration, the EDGE-M3 family of overlapping generations models is heavily calibrated on microeconomic data. This allows the introduction of the underlying individuals' characteristics in a macro model to the greatest extent possible. In particular, it includes the richness of the tax code by means of income tax and social insurance contribution rate functions estimated using data from the EUROMOD microsimulation model. This feature allows in particular a close connection between the macro and the micro model. In addition, the earnings profiles of the seven heterogeneous agent types are estimated using survey data. Finally, the labour supply, bequests and consumption tax calibration are all done using detailed microeconomic data, making the model highly suitable for the analysis of intra- and intergenerational analysis of tax policy.
Keywords: H24; H31; D15; D58; E62; J22; 330; computable general equilibrium; overlapping generations; heterogeneous ability; fiscal policy; microsimulation